2006
DOI: 10.1038/sj.cr.7310068
|View full text |Cite
|
Sign up to set email alerts
|

Upland rice and lowland rice exhibited different PIP expression under water deficit and ABA treatment

Abstract: Aquaporins play a significant role in plant water relations. To further understand the aquaporin function in plants under water stress, the expression of a subgroup of aquaporins, plasma membrane intrinsic proteins (PIPs), was studied at both the protein and mRNA level in upland rice (Oryza sativa L. cv. Zhonghan 3) and lowland rice (Oryza sativa L. cv. Xiushui 63) when they were water stressed by treatment with 20% polyethylene glycol (PEG). Plants responded differently to 20% PEG treatment. Leaf water conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
94
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(103 citation statements)
references
References 40 publications
(52 reference statements)
8
94
1
Order By: Relevance
“…Previous studies have reported the effects of osmotic stress on the expression of aquaporin genes and the genotypic difference in the response of aquaporin gene expression to osmotic stresses (Guo et al, 2006;Lian et al, 2006). However, the study is limited to evaluation of the relationship between aquaporin gene expression that the response of root development to osmotic stress was different in the two cultivars.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies have reported the effects of osmotic stress on the expression of aquaporin genes and the genotypic difference in the response of aquaporin gene expression to osmotic stresses (Guo et al, 2006;Lian et al, 2006). However, the study is limited to evaluation of the relationship between aquaporin gene expression that the response of root development to osmotic stress was different in the two cultivars.…”
Section: Resultsmentioning
confidence: 93%
“…Recent studies have reported that aquaporins facilitate water transport in plant tissues in many plant species (Knipfer et al, 2011;Mahdieh et al, 2008;Murai-Hatano et al, 2008;Sakurai et al, 2008). The regulation of aquaporin gene expression, their trafficking and/or their reversible gating actively regulate the water movement in the plant and play an important role in drought resistance and/or recovery from drought (Matre et al, 2002;Tournaire-Roux et al, 2003;Lian et al, 2006;Guo et al, 2006;Hachez et al, 2013;Luu & Maurel, 2013). These studies indicate that aquaporin OPEN ACCESS previous studies (Sakurai et al, 2005;Sakurai-Ishikawa et al, 2011).…”
mentioning
confidence: 69%
“…However, while overexpression of stress-induced AQPs resulted in improving the plant's stress resistance, expressing AQPs that are down-regulated under abiotic stress had the opposite effect. For example, the rice (Oryza sativa) PIP1 AQP OsPIP1;3 is a stress-induced gene that increases its transcript level in both leaves and roots of the stress-resistant upland rice (subspecies indica cv Zhonghan 3) in response to stress (Lian et al, 2004(Lian et al, , 2006. Overexpressing OsPIP1;3 in the stress-sensitive lowland rice (subspecies japonica cv Zhonghua 11) improved its water status during conditions of water deficit and revealed an increase in whole-plant transpiration and L p (Lian et al, 2004).…”
Section: Root-to-shoot Signaling and Its Impact On G S And A Nmentioning
confidence: 99%
“…Upland rice (Oryza sativa) was germinated in the dark for 3 days at 28°C, and the seedlings grown in nutrient solution at a photon flux density of 300-350 mol m-2s-1, with 60-80% relative humidity,12-h light/12-h dark day-night cycle and 28°C temperature in a phytotron (Lian et al, 2006). Four-week-old plants were used for the different treatments.…”
Section: Plant Materialsmentioning
confidence: 99%